Genomic landscape of B-other acute lymphoblastic leukemia in an adult retrospective cohort with a focus on BCR-ABL1-like subtype - Hrabovsky, Stepan; Vrzalova, Zuzana; Stika, Jiri; Jelinkova, Hana; Jarosova, Marie; Navrkalova, Veronika; Martenek, Jiri; Folber, Frantisek; Salek, Cyril; Horacek, Jan M; Pospisilova, Sarka; Mayer, Jiri; et al. (Acta oncologica (Stockholm, Sweden), 2021)
INTRODUCTION: BCR-ABL1-like acute lymphoblastic leukemia (ALL) is a high-risk disease with a complex genomic background. Though extensively studied, data on the frequency and mutual associations of present mutations are still incomplete in adult patients. This retrospective study aims to map the genomic landscape of B-other ALL in a cohort of adult patients with a focus on the BCR-ABL1-like ALL subtype. METHODS: We analyzed bone marrow and peripheral blood samples of adult B-other ALL patients treated consecutively at three major Czech teaching hospitals. Samples were analyzed by cytogenetic methods, gene expression profiling, multiplex ligation-dependent probe amplification (MLPA), and next-generation sequencing (NGS). RESULTS: Fifty-eight B-other ALL patients (not BCR-ABL1, KMT2A-rearranged, ETV6-RUNX1, TCF3-PBX1, or iAMP21) were included in the study. Median follow-up was 23.8 months. Samples from 33 patients were available for a gene expression analysis, 48.9% identified as BCR-ABL1-like ALL. Of the BCR-ABL1-like ALL cases, 18.8% harbored IGH-CRLF2 and 12.5% P2RY8-CRLF2 fusion gene. We observed a higher MRD failure rate in BCR-ABL1-like than in non-BCR-ABL1-like ALL patients after the induction treatment (50.0 vs. 13.3%, p=.05). There was a trend to worse progression-free and overall survival in the BCR-ABL1-like group, though not statistically significant. Deletions in IKZF1 gene were found in 31.3% of BCR-ABL1-like cases. Patients with concurrent IKZF1 and CDKN2A/B, PAX5 or PAR1 region deletions (IKZF1plus profile) had significantly worse progression-free survival than those with sole IKZF1 deletion or IKZF1 wild-type (p=.02). NGS analysis was performed in 54 patients and identified 99 short variants in TP53, JAK2, NRAS, PAX5, CREBBP, NF1, FLT3, ATM, KRAS, RUNX1, and other genes. Seventy-five of these gene variants have not yet been described in B-cell precursor ALL to date. CONCLUSION: This study widens existing knowledge of the BCR-ABL1-like and B-other ALL genomic landscape in the adult population, supports previous findings, and identifies a number of novel gene variants.
Keywords: genomika; retrospektivní studie; adults; Cohort Studies; Genomics; stanovení celkové genové exprese; Humans; B-other acute lymphoblastic leukemia; BCR-ABL1-like; kohortové studie; next-generation sequencing; Retrospective Studies; akutní lymfatická leukemie; Adult; IKZF1plus; Gene Expression Profiling; Precursor Cell Lymphoblastic Leukemia-Lymphoma; dospělí; lidé